Hoaks, Disinformasi, dan Penegakan Hukum di Ruang Digital: Menimbang Efektivitas Regulasi dan Perlindungan Kebebasan Berekspresi di Indonesia - Gilang Rizki Aji Putra; Sri Ajeng Murni Cahyani Putri (UIN Jakarta, 2025)
The spread of hoaxes and disinformation in the digital sphere threatens social stability, electoral integrity, and public health in Indonesia. This article analyzes the legal framework governing hoaxes and its enforcement in relation to freedom of expression. Using normative legal research, the study finds that Article 28(1) of the Electronic Information and Transactions Law (ITE Law) provides a broad basis for criminal liability, yet its vague wording risks overcriminalizing lawful expression. Key challenges include unclear definitions, limited digital literacy, institutional fragmentation, and the transnational nature of disinformation. Cases involving COVID-19 and the 2024 elections show inconsistent enforcement and evidentiary obstacles. The article concludes that punitive measures alone are insufficient and calls for proportionate enforcement, improved digital literacy, platform cooperation, and institutional reform. Keywords: Hoax, Disinformation, Electronic Information and Transactions Law (ITE Law), Freedom of Expression, Law Enforcement.